Simulasi aliran dua fase pada campuran air-minyak di pipa horizontal dengan parameter termal - Bahrul Jalaali; Eli Kumolosari (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2021)
A CFD study of Water-Oil flow in the horizontal pipe was conducted using the VoF multiphase model coupled with the SST  turbulence model scheme. This study aimed to simulate the mixture flow characteristic by takes account temperature parameter. It was numerically solved using a finite-volume model utilized in Fluent software. The simulation results compared towards experimental showed good prediction on the particular flow pattern. In this study, the thermal parameter was then solved by utilizing energy equation coupled by multiphase model. The water flow temperatures were varied in ranged of 300-340K. The results showed that temperature affected reducing the viscosity of the fluid as well ass the density. Furthermore, the flow pattern changed whereby oil was above the water due to its viscosity and density. This study is beneficial for accessing the temperature effect on the water-oil flow as represented in the applied petroleum industry of oil-lifting.